Penambahan Nori Dalam Proses Pembuatan Tahu Sutera Dari Sari Pati Singkong - Sharas Bhekti Shari; Agus Sholikhin; Alip Suroto (Jurnal Pariwisata Indonesia, 2021)
The research focus on the making process of silk tofu with cassava essence as main ingredients, flavor scoring of silk tofu with cassava essence, and the effect of nori as addition in silk tofu with cassava essence. This is an experimental based research. The data is received from literature study, field observation, and panelists test by expert and intermediate with culinary background. Profesional panelist consist of 2 persons and intermediate profesional panelist consist of 22 persons. The experimental research product results in silk tofu from cassava essence and silk tofu from cassava essence with nori addition. Based on perceived flavor scoring that silk tofu with cassava essence has flavor taste similiarity to silk tofu from soy bean. Based on observatory experimental research found the differ on cost production. Silk tofu from cassava essence has lower cost production compared to silk tofu from soy bean.